Produksi Energi Listrik dari Limbah Kulit Pepaya (Carica papaya) Menggunakan Teknologi Microbial Fuel Cells - Utami, Lisa; Lazulva, Lazulva; Yenti, Elvi (Al-Kimia, 2018)
Microbial Fuel Cells (MFCs) is a technology that can produce electricity whilst at the same time treat wastewater. MFCs convert the chemical energy of organic substrates into electricity through catalyzing the anaerobic oxidation process in the anodic compartment by bacteria as a catalyst. This study investigated the generated electricity using peel papaya (Carica papaya) waste. Peel papaya waste was used as the electron donor in the anaerobic anode compartment and KMnO4 was used as acceptor electron in the cathode compartment with methylene blue as mediators. The maximum power density, current, and voltage respectively were 121, 70 mW/m2, 1,79 ampere and 1,095 V at 17 days operation. The pH of the solution was increased from 3,54 to 6,64 on day 12.